FORMULATION AND PHYSICAL EVALUATION GEL OF AVOCADO SEED (Persea americana Mill.) AS ANTIOXIDANT USING CARBOPOL BASE CONCENTRATION - Maureen Regina Satolom; Paulina Yamlean; Jainer Siampa (PHARMACON, 2023)
Avocado seeds (persea americana mill.) contain flavonoids and have strong antioxidant activity that can help protect organs from toxic agents or oxidative stress. This study aims to formulate, evaluate and test the antioxidant effectiveness of avocado seed extract gel using the DPPH method. This research was conducted experimentally in the laboratory for making avocado seed extract gel formulations (Persea americana Mill.) with a concentration of 0.5%, a concentration of 1%, and a concentration of 1.5% carbopol base. The results showed that the avocado seed ethanol extract gel had IC50 values of 46.05 ppm, 40.01 ppm, 44.80 ppm. Based on the IC50 value obtained, it can be concluded that the avocado seed ethanol extract gel has a very strong antioxidant effectiveness. The SPPS analysis test was continued to see a significant difference but no significant difference was found, therefore the preparation with the lowest concentration will be continued with physical evaluation testing. Physical evaluation of the preparation includes organoleptic observation, pH test, dispersion test, homogeneity test, adhesion test. The results of the physical evaluation test showed that the gel preparation met the requirements.